Some remarks on the success rate data of an extended LL.B. programme for the period 2005-2009 - Dednam, MJ; Dednam, Engela (South African Journal of Higher Education, 2016)
Law faculties is under immense pressure to admit more students but not to produce under-skilled graduates. The endeavour to increase quality by raising the admission requirements is to be balanced by the transformational responsibility to allow access to less prepared school leavers. This led to extended curricula programmes where the admission requirement was lowered and students were allowed to phase into the main stream programme. Investigations initiated in an attempt to answer the question whether the simultaneous running of an extended programme is successful or justified in terms of the eventual results and the additional input that is required included the analysis of a set of data entailing the success rates of the two separate groups of students with respect to each LL.B. module over five years. The purpose of this article is to highlight, interpret and remark on certain findings of the evaluative report. It confirms the expectation that the five year LL.B. groups consistently show a lower success rate than the four year LL.B. groups for the same module groups, but nevertheless an acceptable general level of success, diminishing differences in relative success, and especially the better relative performance in certain modules.